Synthesis and characterization of 2-formylthymol-based azo-aldehyde dyes: Probing their efficacy as a radical scavenger in antioxidant applications - Girase, Kishor Jaysing; Dandge, Santosh Venkatrao; Chaudhari, Mangal Arun; Bendre, Ratnamala Subhash (European Journal of Chemistry, 2025)
A new series of azo-aldehyde dyes has been derived by performing a diazocoupling reaction between 2-isopropyl-5-methyl phenol and diazonium salts obtained by diazotization of differently substituted aromatic amines. The structures of newly synthesized azo-aldehydes were confirmed by modern analytical spectroscopic techniques such as 1H NMR, 13C NMR, FT-IR, and Mass. Thereafter, all synthesized azo-aldehyde dyes were evaluated for their in vitro antibacterial activity against S. aureus, S. typhumurium, E. coli, and P. aeruginosa strains using the plate method. The formed compounds were also evaluated for antioxidant activity. The present results provide new data to support that the thymol-based azo-aldehyde dyes have a potential to explore a variety of applications in the modern field of molecules and materials of high biological relevance.